Pembuatan dan Karakterisasi Edible Film dari Karagenan, Lilin Lebah dan Asam Sitrat - Bayu Meindrawan; Qamarina Yasmin; Vega Yoesepa Pamela (Universitas Teuku Umar, 2020)
The edible film is known as environmentally friendly packaging. Carrageenan has a good barrier property of gases, beeswax as a hydrophobic compound has a good ability to withstand moisture barrier and citric acid as a cross-linking agent which indicate the existence of an ester group. Therefore, the aim of the research is to determine the effect of beeswax and citric acid on the characterization of the carrageenan based edible film. The research was conducted in two stages: fabrication of beeswax emulsion and preparation of edible film from six formulations K, KAS0.25, KAS0.50. KL, KLAS0.25, and KLAS0.50. The result revealed the addition of beeswax and citric acid produced a murky and rough edible film with a grey color. Moreover, the addition of beeswax and 0.50% citric acid significantly improved tensile strength, elongation, and decrease of water vapor transmission rate of carrageenan film. In conclusion, the best formulation was KLAS0.50